Trend following or reversal: Does culture affect predictions and trading behavior? - Rieger, Marc O.; Wang, Mei; Phan, Thuy Chung; Gong, Yujing (Global finance journal, 2022)
We investigate cross-cultural differences in forecasting stock markets and trading tendencies using a survey sample of 339 participants from Switzerland, Ukraine, and China. We find that (1) subjects in all countries exhibit representative bias but in different directions. The Swiss tend to extrapolate recent trends, whereas the Chinese tend to predict reversals. This result is consistent with previous research on cultural lay theories of change. Ukrainian students tend to be optimistic in both up and down markets. (2) Swiss students tend to provide a wider confidence interval in their forecasts than Chinese and Ukrainian students. (3) Subjects from all three countries make similar selling decisions and exhibit the disposition effect, i.e., selling winning stocks while holding losing ones. (4) Concerning buying decisions, Swiss and Chinese students are trend followers. In contrast, Ukrainian students are more likely to buy in both bear and bull markets, perhaps driven by their optimistic view of the future. We did not find a uniform pattern across countries for gender differences in forecast intervals and decision confidence.